Public control in the sphere of corruption counteraction: scientific category and its content - P. A. Kabanov (Russian Journal of Economics and Law)
Objective: to elaborate and theoretically ground the definition of public control in the sphere of corruption counteraction as a legal category. Methods: dialectic method of cognition. Results: Basing on the structural analysis of legal definitions of public control, formulated in the federal and regional legislation of the Russian Federation, as well as in scientific and reference literature, the new definition of public control in the sphere of corruption counteraction as a type of professional activity is proposed. Scientific novelty: The new interpretation of scientific and legal category “public control in the sphere of corruption counteraction” is proposed. Practical value: The elaborated scientific category of public control in the sphere of corruption counteraction allows to reveal the content of this type of activity and may promote further research.